Twolined Spittlebugs in Turfgrass - Eileen A. Buss; Larry Williams (EDIS)
Revised! ENY-334, a 3-page illustrated fact sheet by E.A. Buss and L. Williams, describes the biology and behavior, detection, and control of this pest of centipedegrass and other turfgrasses and ornamentals in northern and northwestern Florida. This revision expands the section on chemical control and updates and restructures the tables of insecticides registered in Florida, separating those registered for homeowners from those registered for professional use. First published by the UF Department of Entomology and Nematology in October 1993, revised June 2006.